Demographic differences in public acceptance of waste-to-energy incinerators in China: High perceived stress group vs. low perceived stress group - Chen, Jiabin; He, Xinyao; Shen, Ye; Zhao, Yiwei; Cui, Caiyun; Liu, Yong (Frontiers in Psychology, 2022)
Demographic characteristics have been recognized as an important factor affecting public acceptance of waste-to-energy (WTE) incineration facilities. The present study explores whether the differences in public acceptance of WTE incineration facilities caused by demographic characteristics are consistent in residential groups under different perceived stress using data collected by a large-scale questionnaire survey (1,066 samples) conducted in three second-tier cities in China. The result of data analysis using a T-test (one-way ANOVA) shows firstly that people with low perceived stress have higher public acceptance of WTE incineration facilities. Second, the differences in public acceptance of WTE incineration facilities caused by demographic characteristics (gender, educational attainment, and age) vary in residential groups with different perceived stress levels. The findings enrich the knowledge system related to demographic characteristics research on NIMBY infrastructure projects and provide the theoretical basis for the government to formulate more targeted policies about NIMBY infrastructure sitting.